How Did Awareness, Emotion, and Motivation Shape Behavior Toward COVID-19 in Tunisians? - Masmoudi, Slim (Frontiers in Public Health, 2021)
This study was conducted to assess the psychological distress in the general population of Tunisia during the epidemic of COVID-19 and examines how awareness of the disease, emotional experience, and motivation shaped the behavior towards this outbreak. The study covers 1492 Tunisian participants. Gender effects and age limits were studied in relation to the seriousness of the disease and lockdown impacts. The data were analyzed and interpreted using the chi-square test, ANOVA, path analysis (PA), and confirmatory factor analysis (CFA). We found a significant effect of gender and age on the awareness of the pandemic dangerousness, the attitude, and the commitment to respect the preventive measures. Women are significantly more aware and committed than men to respect preventive health measures. The 35-45 age group showed more awareness and dedication than the other age groups, while the 20-35 age group showed the most less promise. PA and CFA results showed how awareness, emotion, and motivation shaped behavior towards covid19. This study provides practical and relevant information on behavior change during a pandemic crisis, which can orient communication campaigns and help policymakers.